Antepartum high dietary supply of calcium affects bone homeostasis and offspring growth in dairy sheep and dairy goats - D. Brugger; A. Liesegang (Journal of Dairy Science)
ABSTRACT: This study investigated the effects of high dietary Ca supplementation during the final 21 d antepartum on Ca and bone homeostasis in dairy sheep and goats, and the growth response of their suckling offspring. Multiparous dairy sheep (n = 5/group, 10 animals total) and goats (n = 6/group, 12 animals total) were randomly assigned to 2 experimental groups. Feeding occurred restrictively (2.3 kg DM/d per animal antepartum for both species; 2.9 and 3.1 kg DM/d per animal for sheep and goats postpartum, respectively) according to recommendations, except for Ca during antepartum feeding: 1 group received the basal diet based on hay and concentrate with extra CaCO3 (1.3% Ca in DM; 2.49-fold the recommendations) for 3 wk antepartum, whereas the other group received only the basal diet (0.6% Ca in DM; 1.15-fold the recommendations). Experimental feeding ended with parturition, and animals were henceforth fed according to Swiss recommendations for lactating sheep and goats and kept together with their suckling offspring. The observation period spanned from 21 d antepartum to 56 d postpartum. Animals were under continuous veterinary surveillance and were monitored for signs of milk fever. Data collection comprised quantitative and functional parameters of Ca and bone homeostasis, as well as birth weights and daily weight gain of suckling lambs and kids. Data were analyzed using repeated measures and endpoint mixed models. The response of quantitative markers indicated that high dietary Ca antepartum significantly increased fecal Ca concentrations until parturition, suggesting efficient physiological mechanisms to manage Ca overload through increasing fecal excretion. No significant differences were observed in serum Ca levels, urinary Ca excretion, or bone mineral density between the antepartum Ca feeding groups at any point during the observation period, indicating stable Ca homeostasis, despite the dietary challenge. Differences in quantitative markers were noted between sheep and goats, including variations in serum and colostral Ca levels and bone mineral density, which largely aligned with results from earlier comparative studies. Serum 1,25-(OH)2 vitamin D (calcitriol) as well as markers of bone formation and resorption were monitored, revealing significant increases in serum osteocalcin postpartum in both goats and sheep fed high Ca antepartum. However, all other serum markers, including calcitriol, remained unaffected by the feeding regimen but differed between sheep and goats, consistent with previous findings. All repeated measures were significantly affected by time, except for urinary Ca and bone-specific alkaline phosphatase activity in serum. Suckling offspring of sheep and goats in the high Ca group exhibited significantly reduced average daily weight gain compared with those in the group that received 0.6% in DM Ca, despite similar birth weights. We conclude that although dairy sheep and goats effectively managed high dietary Ca intake without overt signs of hypocalcemia or milk fever under these experimental conditions, the observed effects on offspring growth and potential long-term physiological effects warrant further investigation. These findings contribute to the understanding of mineral nutrition in late-gestating dairy goats and sheep and highlight the need for further research on balanced dietary strategies to optimize health and productivity of dairy sheep and goats and their offspring.